UPAYA PENINGKATAN KOMPETENSI GURU MATA PELAJARAN DALAM MENYUSUN PERANGKAT PEMBELAJARAN MELALUI KEGIATAN MGMP DI SMPN 28 KABUPATEN TEBO - AHMAD APENDI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2023)
This study aims to determine the effectiveness of the MGMP as a forum for meeting teachers of similar subjects to solve problems, especially in terms of making lesson plans for the 2013 curriculum. This research was carried out for 3 months from August to November 2021. To see the effectiveness of activities, the School MGMP was carried out for eye teachers subjects in the National Examination, such as Indonesian, Mathematics, English and Science, totaling 21 teachers. This research was conducted for two cycles, each cycle consisting of planning, implementation, observation and reflection stages. The reflection results of the first cycle are then used as a prefix for the second cycle and so on. To see the results of the subject teachers' work in making lesson plans for Curilas, a study of the lesson plans was carried out using the lesson plans study format, totaling 8 items and 43 indicator items. The results of the study of the RPP using the RPP format consist of 8 items, namely Subject Identity, Core Competencies and Basic Competencies, Formulation of Indicators, Formulation of Learning Objectives, Selection of Teaching Materials, Selection of learning resources, Selection of Learning Media, Learning Models, Learning Methods, Scenarios Learning and Design Learning assessment, with a scale of 1 to 3. Provisions are given a score of 1 if it is not appropriate / incomplete, given a score of 2 if it is partially appropriate or incomplete, and given a score of 3 if it is appropriate or complete. Of the 8 items described in 41 instrument items, so that the maximum score is 123 points. The results of this research in cycle 1 obtained a total value of 1730.89 with an average value of 82.27. The highest score was 96.75 while the lowest score was 72.36. The results of the second cycle of research from the 8 items are described in 41 instrument items, so that the maximum score is 123 points. The results of this study in cycle 2 obtained a total value of 1956.10 with an average value of 93.15. The highest score was obtained at 99.19 while the lowest score was 82.11. The data obtained was then processed using SPSS ver. 20.0 to obtain an overview and dissemination of the data obtained. ABSTRAKPenelitian ini bertujuan mengetahui efektifitas MGMP sebagai wadah peetemuan Guru mata pelajaran sejenis untuk memecahkan masalah, terutama dalam hal pembuatan RPP kurikulum 2013. Penelitian ini dilaksanakan selama 3 bulan sejak bulan Agustus sampai November 2021. Untuk melihat efektifitas kegiatan, maka MGMP Sekolah dilaksanakan pada guru mata pelajaran yang di Ujian Nasionalkan, seperti Bahasa Indonesia, Matematika, Bahasa Inggris dan IPA, berjumlah 21 orang guru. Penelitian ini dilaksanakan selama dua siklus, tiap siklusnya terdiri dari tahap perencanaan, pelaksanaan, observasi dan refleksi. Hasil refleksi siklus pertama kemudian dijadikan awalan bagi siklus kedua dan seterusnya. Untuk melihat Hasil keja Guru mata Pelajaran dalam membuat RPP Kurilas, maka dilakukan penelahaan RPP dengan menggunakan format telaah RPP, sebanyak 8 item dan 43 butir indikator. Hasil telaah RPP dengan menggunakan format telah RPP yang terdiri dari 8 item yaitu Identitas Mata pelajaran, Kompetensi Inti dan Kompetensi Dasar, Petumusan Indikator, Perumusan Tujuan pembelajaran, Pemilihan Bahan ajar, Pemilihan sumber belajar, Pemilihan Media Belajar, Model Pembelajaran, Metode Pembelajaran, Skenario Pembelajaran dan Rancangan Penilaian pembelajaran, dengan skala 1 sampai 3. Ketentuan diberi skor 1 jika tidak sesuai / tidak lengkap, diberi skor 2 jika Sesuai sebagian atau kurang lengkap, dan diberi skor 3 jika sesuai atau lengkap. Dari 8 item tersebut diuraikan dalam 41 butir instrumen, sehingga skor maksimal sebesar 123 point. Hasil penelitian pada siklus 1 ini diperoleh jumlah nilai 1730, 89 dengan rata rata nilai 82,27. Nilai tertinggi diperoleh sebesar 96,75 sedangkan skor terendah sebesar 72,36. Hasil penelitian siklus kedua Dari 8 item tersebut diuraikan dalam 41 butir instrumen, sehingga skor maksimal sebesar 123 point. Hasil penelitian pada siklus 2 ini diperoleh jumlah nilai 1956,10 dengan rata rata nilai 93,15. Nilai tertinggi diperoleh sebesar 99,19 sedangkan skor terendah sebesar 82,11 Data yang diperoleh kemudian diolah dengan menggunakan SPSS ver. 20.0 untuk memperoleh gambaran dan penyebaran data yang diperoleh.